Inundation depth stimulates plant‐mediated CH4 emissions by increasing ecosystem carbon uptake and plant height in an estuarine wetland. (1st February 2023) - Zhao, Mingliang; Li, Peiguang; Song, Weimin; Chu, Xiaojing; Eller, Franziska; Wang, Xiaojie; Liu, Jingtao; Xiao, Leilei; Wei, Siyu; Li, Xinge; Han, Guangxuan
Abstract: Plant‐mediated CH4 emission is an important part of the ecosystem CH4 emission from vegetated wetlands. Inundation depth may alter the potential magnitude of CH4 releases by changing CH4 production and plant transport, but the relationships between plant‐mediated CH4 emissions and inundation depth are still uncertain, especially for estuarine wetlands with changeable hydrological processes. Besides, there are conflicting results regarding the role of inundation depth in plant‐mediated CH4 emissions. Here we conducted a novel inundation depth experiment (0, 5, 10, 20, 30 and 40 cm inundation depth) dominated by Phragmites australis in the Yellow River estuary, China. Soil CH4 emissions, ecosystem CH4 emissions, net ecosystem CO2 exchange (NEE), soil organic carbon (SOC) and plant traits were measured during the growing seasons of 2018, 2019 and 2020. Plant‐mediated CH4 emissions were the difference between ecosystem CH4 emissions and soil CH4 emissions. The results showed that inundation depth decreased soil CH4 emissions but increased ecosystem CH4 emissions. Plant‐mediated CH4 transport from Phragmites australis accounted for 99% of total ecosystem CH4 emissions under different inundation depths. Inundation depth strongly stimulated plant‐mediated CH4 emission from 0 to 20 cm during the growing seasons. The increased NEE enhanced plant‐mediated CH4 emissions by altering production, suggesting that carbon components derived from photosynthetic carbon input may benefit CH4 production. Additionally, the increased plant height promoted CH4 emission by regulating plant transport, indicating that plant traits may play an important role in transport of CH4 . Our findings indicated that NEE and plant height play an important role in plant‐mediated CH4 emissions under different inundation depths in estuarine wetland. This study also highlights that hydrological regimes and plant traits are essential for the estimation of CH4 emissions in future projections of global wetland changes. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog.